2012
DOI: 10.1155/2012/942784
|View full text |Cite
|
Sign up to set email alerts
|

On the Performance of Hybrid PV/Unitized Regenerative Fuel Cell System in the Tropics

Abstract: Solar hydrogen system is a unique power system that can meet the power requirements for future energy demands. Such a system uses the hydrogen as the energy carrier, which produces energy through the electrolyzer with assistance of the power from the PV during the sunny hours, and then uses stored hydrogen to produce energy through the fuel cell after sunset or on cloudy days. The current study has used premanufactured unitized regenerative fuel cells in which the electrolyzer and the fuel cell function within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…It is extremely important to consider this factor in designing any PV system as it may cause a serious undersizing problem. According to [20][21][22][23][24][25], the average performance factor of PV systems in the selected testing field is about 67.2%. This result is further supported by this research, whereas the average performance factor of the tested module is found to be about 63.4%.…”
Section: Discussionmentioning
confidence: 99%
“…It is extremely important to consider this factor in designing any PV system as it may cause a serious undersizing problem. According to [20][21][22][23][24][25], the average performance factor of PV systems in the selected testing field is about 67.2%. This result is further supported by this research, whereas the average performance factor of the tested module is found to be about 63.4%.…”
Section: Discussionmentioning
confidence: 99%
“…The electrical performance, gas production, work efficiency, operation stability, and cycle life are important parameters to measure the performance of cells and fuel cell stacks. A number of scholars have conducted experimental studies on the electrical performance , and gas production volume , of the single cell, and studies showed that the increase of electrolytic voltage and current density was conducive to the increase of the gas production volume of the electrolytic cell mode . The solid–liquid and gas–liquid interfaces in PEMFCs were studied, which indicated that the liquid water inside the PEMFC had a great impact on the fuel cell.…”
Section: Introductionmentioning
confidence: 99%
“…A number of scholars have conducted experimental studies on the electrical performance 2,3 and gas production volume 4,5 of the single cell, and studies showed that the increase of electrolytic voltage and current density was conducive to the increase of the gas production volume of the electrolytic cell mode. 4 The solid− liquid and gas−liquid interfaces in PEMFCs were studied, 6 which indicated that the liquid water inside the PEMFC had a great impact on the fuel cell. Proton exchange membrane (PEM) ECs were often used in combination with solar power systems as an important part of energy storage and oxygen production equipment.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the URFC has been investigated for space applications 6,7 and hybrid power systems. 8,9 Up to now, abundant works on URFCs have been done. However, much attentions have been paid to catalyst, 10,11 bifunctional electrode, 12,13 gas diffusion layer, 14,15 and bipolar plate.…”
Section: Introductionmentioning
confidence: 99%
“…To promote the practical applications, URFC stacks have been developed. Besides, the URFC has been investigated for space applications and hybrid power systems . Up to now, abundant works on URFCs have been done.…”
Section: Introductionmentioning
confidence: 99%